Preparation and Characterization of Cholesterol Esterase Inhibition Protein Hydrolysate from Whiteleg Shrimp (Litopenaeus vannamei) Head - Vo, Bao Chi; Nguyen, Ha Thu; Vo, Linh Thi Truc; Cao, Khang Tran Gia; Vo, Tam Dinh Le (Universitas Gadjah Mada, 2026)
Protein hydrolysates with cholesterol esterase inhibition activity (CEIA) can reduce the de-esterification and absorption of dietary cholesterol, helping manage hypercholesterolemia. With a high protein content, whiteleg shrimp (Litopenaeus vannamei) heads (WLSH) are a promising source for producing such hydrolysates. Using a single-factor test by sequentially varying WLSH powder-to-water ratio (1:3–1:8 w/v), enzyme-to-substrate (E:S) ratio (10–50 U/g protein), and hydrolysis time (2–7 h), the best alcalase-catalyzed hydrolysis condition was determined as a 1:6 (w/v) WLSH powder-to-water ratio, a 30 U/g protein E:S ratio, and a 4-h hydrolysis time. The resulting hydrolysate displayed a CEIA of 58.00 ± 0.64% and retained over 70% of its activity after treatment with pH (1.0–6.0) or heat (100 °C for 2 h). Arg, the predominant amino acid in the hydrolysate, together with abundant hydrophobic amino acids, contributed to the hydrolysate’s activity. Furthermore, the notable foaming and emulsifying properties of the hydrolysate indicate its promise as a surface-active agent in food applications. Besides, the 1–3 kDa fraction from the hydrolysate exhibited the greatest CEIA, probably due to its easier access to the enzyme’s active site. With higher CEIA, compared to other hydrolysates, the WLSH hydrolysate and its 1–3 kDa fraction could serve as a new natural cholesterol-lowering agent.